2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Breaking LTE on Layer Two

Abstract: Long Term Evolution (LTE) is the latest mobile communication standard and has a pivotal role in our information society: LTE combines performance goals with modern security mechanisms and serves casual use cases as well as critical infrastructure and public safety communications. Both scenarios are demanding towards a resilient and secure specification and implementation of LTE, as outages and open attack vectors potentially lead to severe risks. Previous work on LTE protocol security identified crucial attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 33 publications
0
106
0
Order By: Relevance
“…In contrast, our ToRPEDO exploits the protocol standard's vulnerability of choosing fixed paging frames for a subscriber which makes all the network operators vulnerable to this attack. Rupprecht et al [31] and Jover et al [32] demonstrated that an adversary can identify victim UE's short-lived, lower-layer identifier (C-RNTI) when given the UE's TMSI and thus track the victim's UE. ToRPEDO, on the contrary, recovers the UE's PFI (and TMSI as a side effect) which enables tracking victim's UE irrespective of short-lived C-RNTIs or TMSIs.…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, our ToRPEDO exploits the protocol standard's vulnerability of choosing fixed paging frames for a subscriber which makes all the network operators vulnerable to this attack. Rupprecht et al [31] and Jover et al [32] demonstrated that an adversary can identify victim UE's short-lived, lower-layer identifier (C-RNTI) when given the UE's TMSI and thus track the victim's UE. ToRPEDO, on the contrary, recovers the UE's PFI (and TMSI as a side effect) which enables tracking victim's UE irrespective of short-lived C-RNTIs or TMSIs.…”
Section: Related Workmentioning
confidence: 99%
“…In LTE, this task is facilitated by the lack of Media Access Control (MAC) and Radio Link Control (RLC) encryption. Thus, subscribers may be de-anonymized [2] or User Equipment (UE) locations can be tracked [3]. In case of stationary UEs, e.g.…”
Section: A Jammer Propertiesmentioning
confidence: 99%
“…The existence of LTE protocol vulnerabilities has been known for some time, although these have not been publicly discussed until recently. The openness of the standard, the large community of researchers, and the broad availability of SDRs, software libraries and open-source implementations of both the eNodeB and the UE protocol stacks have enabled a number of excellent LTE security analyses [5], [9], [10], [28], [29]. Despite the stronger cryptographic algorithms and mutual authentication, UEs and base stations exchange a substantial amount of pre-authentication messages that can be exploited to launch denial of service (DoS) attacks [6], [14], [30], catch IMSIs [31] or downgrade the connection to an insecure GSM link [7], [10].…”
Section: A Lte Protocol Exploitsmentioning
confidence: 99%
“…Nevertheless, a series of vulnerabilities inherent to the LTE protocol still exist and have been identified by researchers over the last few years. For example, a substantial number of pre-authentication messages are sent in the clear, which can be exploited to launch Denial of Service (DoS) attacks and obtain location information of mobile subscribers [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation